Pandemic narratives: perception and preparation of body in the contemporary dance scene in São Paulo (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Body' artists faced challenges in reinventing their production methods, also dealing with the absence of physical presence during the covid-19 pandemic. This disrupted and mobilized alternative modes of body perception and preparation, impacting the contemporary dance scene. Through Narrative Interviews, we listened to individuals who produced dance in this scenario, including two representatives from official companies and 15 from independent nuclei in São Paulo. We aimed at giving visibility to artists’ voices and how they signified their experience of the dancing body in that period.
Keywords: body; preception; preparation; contemporary dance